Imprensa e história no Rio de Janeiro dos anos 50 - Ribeiro, Ana Paula Goulart (2000)
The 1950s was a decade of profound change in Brazilian journalism, particularly in Rio de Janeiro. It was the time when the North American model took root in Brazilian journalism and brought about not only the modemization of the companies and the texts printed, but also greater professionalization of the journalists themselves and the elaboration of a whole ethos regarding the essence of journalism and its social function. Taken as a whole, these reforms led to a process of increased autonomy of the joumalistic milieu, particularly with respect to the political and literary spheres. To what extent though, did these transformations constitate a radical break with the former way of doing journalism? What was there in terms of structural innovation, and how much were they merely a continuation of what went before? What is the significance of the whole package, namely administrative, editing, publishing, printing and professional reforms? What was the driving force behind them? Was the process of transformation in joumalism on similar lines to that taking place in the leading capitalist nations? Could it be that the streamlining of production processes had paved the way for the institution of mass journalism in Brazil and for the incorporation of the press in the sphere of the cultural industry? Or, should we deduce that the modernization of Brazilian journalism was impelled by motives from an entirely different source?